2015
DOI: 10.1007/s11250-015-0867-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of recombinant LigB protein and heat-killed antigen-based latex agglutination test with microscopic agglutination test for diagnosis of bovine leptospirosis

Abstract: This study aimed to develop latex agglutination test (LAT) using recombinant leptospiral immunoglobulin-like protein (LigB) (rLigB) antigen and compare its diagnostic efficacy with LAT using conventional heat-killed leptospiral antigen and microscopic agglutination test (MAT) in diagnosing bovine leptospirosis. The PCR-amplified 1053-bp ligB gene sequences from Leptospira borgpetersenii Hardjo serovar were cloned in pET 32 (a) vector at EcoRI and NotI sites and expressed in BL21 E. coli cells as fusion protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Therefore, rLoa22 LAT can be used as a preliminary screening test for the detection of anti-leptospiral antibodies in the sera of bovine and dogs suspected of leptospirosis before carrying out the MAT. Nevertheless, further isolation from the dam and aborted fetuses are needed to establish the part of Leptospira contribution in causing abortion and stillbirth in bovine (Nagalingam et al 2015;Balamurugan et al 2018) as MAT alone is not a suitable test for the diagnosis of leptospirosis as stated by Limmathurotsakul et al (2012). As the test can be used as a screening test for the detection of anti-leptospiral antibodies, if the test result is positive, it needs to be rechecked with another confirmatory test as reported earlier (Alamuri et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, rLoa22 LAT can be used as a preliminary screening test for the detection of anti-leptospiral antibodies in the sera of bovine and dogs suspected of leptospirosis before carrying out the MAT. Nevertheless, further isolation from the dam and aborted fetuses are needed to establish the part of Leptospira contribution in causing abortion and stillbirth in bovine (Nagalingam et al 2015;Balamurugan et al 2018) as MAT alone is not a suitable test for the diagnosis of leptospirosis as stated by Limmathurotsakul et al (2012). As the test can be used as a screening test for the detection of anti-leptospiral antibodies, if the test result is positive, it needs to be rechecked with another confirmatory test as reported earlier (Alamuri et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of early detection of leptospirosis by simple and rapid test, an attempt was made to develop rapid field diagnostics as a preliminary screening test using recombinant OMP (LigB and Lsa27 proteins) for the detection of anti‐leptospiral antibodies in the sera of bovine (Nagalingam et al . 2015; Alamuri et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the crossed reactions shown by the latex tests, it is important to highlight that studies have demonstrated the existence of a very good correlation with similar specificity and sensitivity results among different techniques for the same diagnostic test. This is why these tests are considered highly promising to be used-especiallyin rapid and economic screening processes, which can be conducted in the field and do not require sophisticated equipment or specialized technical personnel (Nagalingam et al 2015;Senthilkumar et al 2010;Uslu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hiện nay, cùng với sự phát triển của công nghệ DNA tái tổ hợp, sản xuất các kháng nguyên tái tổ hợp của Leptospira trong chẩn đoán Leptospira bằng ELISA đã được báo cáo. Kết quả cho thấy các bộ kít ELISA sử dụng các kháng nguyên rLipL32/1-LipL21-OmpL1/2 (Qiu et al, 2008), LipL41 (Ambily et al, 2019 và LigA, LigB (Nagalingam et al, 2015;Shekatkar et al, 2010) có thể áp dụng trong phát hiện Leptospira ở giai đoạn sớm. Trong các kháng nguyên của Leptospira, sử dụng LigA và LigB làm nguyên liệu chế tạo bộ kít ELISA có độ nhạy và độ đặc hiệu cao và đây được xem là nguồn vaccine tiềm năng cho phòng bệnh Leptospirosis trên người cũng như được đánh giá là marker cho chẩn đoán nhiễm Leptospira ở giai đoạn cấp (Croda et al, 2007;Palaniappan et al, 2004).…”
Section: đặT Vấn đềunclassified